The Concept of Istidraj in the Qur'an: Comparative Study of the Interpretation of Al-Imam Al-Qurtubi and Shaikh Wahbah Al-Zuhaily - Fauzi Fathur Rosi; Pajar Amirul Mu’ti (World Journal of Islamic Learning and Teaching, 2024)
Happiness is one of the natural attitudes of humans when getting a lot of pleasure from Allah SWT, such as health and sustenance. However, not many of humans are correct in responding to these blessings, pleasures that are not properly addressed are termed istidraj. Istidraj is a punishment given by Allah SWT to the perpetrators of immorality in the form of worldly pleasures that seem beautiful but cause negligence in the real world. Therefore, it is necessary to be aware of istidraj as a sign of caution in order to avoid immoral acts. The phenomenon of istidraj in this study explores the concept of this in the Qur'an through the perspective of two mufasirs, namely al-Imam al-Qurtubi and Wahbah al-Zuhaily in answering 2 focuses, namely: 1. How to interpret istidraj in the Qur'an according to al-Imam al-Qurtubi and Wahbah al-Zuhaily 2. What are the similarities and differences between al-Imam al-Qurtubi and Wahbah al-Zuhaily regarding istidraj. To understand the concept of the istidraj phenomenon, this study applies a qualitative method of literature study with a comparative study approach. In this approach, the researcher compares the interpretation of al-Imam al-Qurtubi through the tafsir "Al-Jami' li al-Ahkam al-Qur'an" with the interpretation of Wahbah al-Zuhaily through the tafsir "Al-Tafsir al-Munir". The researcher examined the interpretation data from the two mufasirs related to the concept of istidraj. A comparative approach is used to gain a deeper understanding and see the differences and similarities in the views of the two towards istidraj. As for the results of this research, al-Qurtubi sees istidraj as a gradual punishment process for those who deny the verses of Allah SWT. Wahbah al-Zuhaily sees it as a gift of favor or success. Both mufasirs agree that istidraj involves giving pleasure as a test of Allah. The difference in interpretation lies in the context of the object of istidraj. al-Zuhaily emphasizes his interpretation on the test of a servant, while al-Qurtubi emphasizes the interpretation of istidraj on slow withdrawal as punishment.